The Development of E-Learning-Based Collaboration (KABEL) - Ida Kaniawati; Maryani; Heny Ekawati Haryono; Iib Marzuqi (Studies in Learning and Teaching, 2023)
E-learning-based collaboration (KABEL) can be used as an alternative to improve learning outcomes and student cooperation. This study aims to develop high school physics learning tools using e-learning based collaboration model in the form of lesson planning, student worksheet, teaching materials and learning outcomes on heat material. The method used is development research 4-D development models (Define, Design, Develop, Disseminate). The results of the study show: 1) The validation of learning devices achieves very valid criteria; 2) The practicality of learning devices is determined through the implementation of learning at 87% with very good criteria and student response questionnaires at 83.77% with good criteria; 3) The effectiveness of learning devices is determined through student activities at 83.64% with good criteria and student learning outcomes in temperature and heat at 45 with criteria N-gain medium. Thus, it was concluded that the design of learning devices using collaborative learning models based on e-learning heat material is valid, practical, and effective criteria.